Antioxidant metabolism regulates CD8+ T memory stem cell formation and antitumor immunity - Pilipow, Karolina; Scamardella, Eloise; Puccio, Simone; Gautam, Sanjivan; De Paoli, Federica; Mazza, Emilia M. C.; De Simone, Gabriele; Polletti, Sara; Buccilli, Marta; Zanon, Veronica; Di Lucia, Pietro; Iannacone, Matteo; et al. (JCI Insight, 2018)
Adoptive T cell transfer (ACT) immunotherapy benefits from early differentiated stem cell memory T (Tscm) cells capable of persisting in the long term and generating potent antitumor effectors. Due to their paucity ex vivo, Tscm cells can be derived from naive precursors, but the molecular signals at the basis of Tscm cell generation are ill-defined. We found that less differentiated human circulating CD8+ T cells display substantial antioxidant capacity ex vivo compared with more differentiated central and effector memory T cells. Limiting ROS metabolism with antioxidants during naive T cell activation hindered terminal differentiation, while allowing expansion and generation of Tscm cells. N-acetylcysteine (NAC), the most effective molecule in this regard, induced transcriptional and metabolic programs characteristic of self-renewing memory T cells. Upon ACT, NAC-generated Tscm cells established long-term memory in vivo and exerted more potent antitumor immunity in a xenogeneic model when redirected with CD19-specific CAR, highlighting the translational relevance of NAC as a simple and inexpensive method to improve ACT.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Cancer immunotherapy; Cellular immune response; Immunology; T cells